2017
DOI: 10.1063/1.4982949
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy and formation of lanthanum-hydrocarbon radicals formed by C—C bond cleavage and coupling of propene

Abstract: La reaction with propene is carried out in a laser-vaporization molecular beam source. Three Lahydrocarbon radicals are characterized by mass-analyzed threshold ionization (MATI) spectroscopy. One of these radicals is methylenelanthanum [La(CH 2)] (C s), a Schrock-type metal carbene. The other two are a five-membered 1-lanthanacyclopent-3-en [La(CH 2 CHCHCH 2)] (C s) and a tetrahedron-like trimethylenemethanelanthanum [La(C(CH 2) 3)] (C 3v). Adiabatic ionization energies and metal-ligand stretching and hydroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…We have extensively used the DFT/B3LYP method and found that this method generally produced adequate results for spectral and structural assignments of organometallic radicals. [63][64][65][66][67][68][69][70]86 No symmetry restrictions were imposed in initial geometry optimizations, but appropriate point groups were used in subsequent optimizations to help identify electronic symmetries. The geometry of each stationary point was obtained through a relaxed potential energy surface scan along the proposed reaction coordinates.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have extensively used the DFT/B3LYP method and found that this method generally produced adequate results for spectral and structural assignments of organometallic radicals. [63][64][65][66][67][68][69][70]86 No symmetry restrictions were imposed in initial geometry optimizations, but appropriate point groups were used in subsequent optimizations to help identify electronic symmetries. The geometry of each stationary point was obtained through a relaxed potential energy surface scan along the proposed reaction coordinates.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Because of low ablation laser power, no La clusters were produced except for very small amounts of La 2 , La 2 C, and La 2 O 1,2 . La oxides could be formed by La reactions with oxygen that is present in the carrier gas as an impurity or by laser vaporization of La oxide impurity in the La rod, [63][64][65][66][67][68][69] whereas the La carbide could be associated with La reactions with the vapor of diffusion pump oil. The mass spectra from the two pentene reactions are essentially the same and show a predominant product La(C 5 H 8 ), a significant amount of La (C 10 H 18 ), and two minor species La(C 2 H 2 ) and La(C 3 H 4 ).…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 3 more Smart Citations